Ecoresponsible actions in operating rooms: A health ecological and economic evaluation. (May 2022) - Rouvière, N.; Chkair, S.; Auger, F.; Alovisetti, C.; Bernard, MJ.; Cuvillon, P.; Kinowski, J-M.; Leguelinel-Blache, G.; Chasseigne, V.
Abstract: Background: In the current context of climate change, actions must be taken to improve the hospital's ecological footprint, particularly in the operating room, which is a major consumer of medical devices. Methods: This prospective pilot study assessed the ecological and economic impacts of sustainable actions targeting medical devices designed by a multidisciplinary working group and implemented in the 24 operating rooms of a University Hospital over one year. The ecological analysis was based on the life cycle assessment method and categorized in seven impacts. The economic impact was assessed by a micro-costing analysis and divided in four main expense items: human and material resources, logistics, and waste management. Results: In total, 13 actions were implemented with the aim of reducing waste volume, improving waste sorting, and increasing eco-responsible purchases. In one year, these 13 actions allowed avoiding the emission of 203 tons eq CO2 . The environmental and human toxicity benefits were 707.8 and 156.2 tons of 1.4 dichlorobenzene, respectively. Concerning non-renewable resources, these actions avoided the extraction of 9 tons of oil (petroleum) and 610 kg of copper per year. These actions led to a land occupation reduction of 1071.3 m 2 year and to water saving of 552 m 3 . From the economic side, the implementation of these actions brought a gain of €3747.9 for the first year and of €5188.2 for the following years. Conclusion: The integration of sustainable measures in operating rooms leads to important ecological benefits and also generating savings. This more eco-responsible approach should be considered in all healthcare establishments that generate a significant annual volume of waste. Highlights: In the current context of climate change, actions must be taken to improve the hospital's ecological footprint, particularly in the Operating Room (OR). The implementation of targeted actions on the medical device makes it possible to considerably reduce CO2 emissions and water consumption while saving natural resources. The integration of sustainable measures in OR also generates savings for the Hospital.